In vitro sensitivity reduction of Fusarium graminearum to DMI and QoI fungicides - Avozani,Aveline (2014)
In Brazil, Fusarium head blight (FHB) affecting wheat can cause up to 39.8% damage. Resistant cultivars are not available yet; thus, short-term disease control relies on the use of fungicides. The first step to improve control is to monitor fungal populations that are sensitivity to chemicals in order to achieve efficient FHB management. In vitro experiments were conducted to evaluate the inhibitory concentration (IC50) of fungicides for both mycelial growth and conidial germination of ten Fusarium graminearum isolates. The following demethylation inhibitor (DMI) fungicides were tested: metconazole, prothioconazole and tebuconazole. In addition, pyraclostrobin and trifloxystrobin were included, representing QoI fungicides, as well as three co-formulations containing metconazole + pyraclostrobin, prothioconazole + trifloxystrobin, and tebuconazole + trifloxystrobin. For mycelial growth, the overall mean IC50 of isolates was: metconazole 0.07, prothioconazole 0.1, and tebuconazole 0.19 mg/L. For the co-formulations, it was: prothioconazole + trifloxystrobin 0.08, tebuconazole + trifloxystrobin 0.12, and metconazole + pyraclostrobin 0.14 mg/L. Regarding spore germination inhibition, IC50 for prothioconazole + trifloxystrobin was 0.06, for tebuconazole + trifloxystrobin, 0.12 mg/L, for QoI alone pyraclostrobin, was 0.09, and for trifloxystrobin, 0.28 mg/L. There was a sensitivity shift among isolates and the highest fungitoxicity to F. graminearum was confirmed for prothioconazole, metconazole and tebuconazole .